2008
DOI: 10.1177/1352458508097923
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme (ACE) and ACE2 levels in the cerebrospinal fluid of patients with multiple sclerosis

Abstract: These results further indicate an alteration of the intrathecal renin-angiotensin system in patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 10 publications
0
46
0
1
Order By: Relevance
“…Increased levels of ACE2 and Ang-(1-7) were found in the cerebrospinal fluid of multiple sclerosis patients. 90 Moreover, Lu et al 91 showed that chronic central administration of Ang-(1-7) reduces the infarct area and provides cerebroprotection following focal cerebral ischemia/reperfusion in rats. The authors suggest that the heptapeptide modulates in vivo NO release and eNOS expression in this stroke model.…”
Section: Redox-sensitive Signaling By the Ace2-ang-(1-7)-mas Axismentioning
confidence: 99%
“…Increased levels of ACE2 and Ang-(1-7) were found in the cerebrospinal fluid of multiple sclerosis patients. 90 Moreover, Lu et al 91 showed that chronic central administration of Ang-(1-7) reduces the infarct area and provides cerebroprotection following focal cerebral ischemia/reperfusion in rats. The authors suggest that the heptapeptide modulates in vivo NO release and eNOS expression in this stroke model.…”
Section: Redox-sensitive Signaling By the Ace2-ang-(1-7)-mas Axismentioning
confidence: 99%
“…In the chronic stage of MS, perivascular astrocytes are progressively lost [6], rendering the BBB leaky. The reduction of angiotensin II levels in the CSF that we observed may in part reflect such a process [3,7].…”
Section: Introductionmentioning
confidence: 67%
“…We previously reported an increase in the level of ACE and a decrease in the level of ACE2 in MS patients without anti-AQP4 antibody [7], and suggested a compensatory mechanism to be operative in response to a decrease in the level of angiotensin II, namely, up-regulation of the synthesizing enzyme (ACE) and downregulation of the catabolizing enzyme (ACE2). Although we could not reproduce the increase in ACE level in this series of MS patients, at least the ACE level was not decreased as compared with that in controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that cerebrospinal fluid levels of angiotensin and angiotensin-converting enzymes produced and secreted from astrocyte end feet were significantly decreased in NMO [148] and MS [149,150] patients, suggesting that injury to astrocyte end feet and dampening of astrocytic barrier functions may occur in both MS and NMO.…”
Section: Neuroprotective Aspectsmentioning
confidence: 93%